Improvement in quality of life and cognitive function in Post-COVID syndrome after online occupational therapy: Results from a randomized controlled pilot study. - Dominik Schröder; Andrea Stölting; Christina Müllenmeister; Georg M N Behrens; Sandra Klawitter; Frank Klawonn; Aisha Cook; Nadja Wegner; Martin Wetzke; Tim Schmachtenberg; Alexandra Dopfer-Jablonka; Frank Müller; et al. (PLoS ONE, 2025)
Background Post-COVID syndrome (PCS) poses enormous clinical challenges. Occupational therapy (OT) is recommended in PCS, but structural validation of this concept is pending. Methods In an unblinded randomized pilot study (clinical trial # DRKS0026007), feasibility and effects of online OT in PCS were tested. Probands received structured online OT over 12 weeks either via interactive online treatment sessions (interactive group) or prerecorded videos (video group). 50% of probands received no online OT (control group). At week 0, 12, and 24, we analyzed study experience, health-related quality of life, cognitive functions. impairment in performance, and social participation. Results N = 158 probands (mean age 38 yrs., 86% female) were included into the analyses. The study experience was described as positive or very positive in 83.3% of probands in the interactive versus 48.1% of probands in the video group (p = 0.001). After 12 weeks, all groups displayed significant improvement in concentration, memory, and performance of daily tasks. After 24 weeks, significant improvement in concentration and memory were observed in control- and video-probands, and social participation had improved after video-OT. However, only probands in the interactive online OT group showed improvement of all measured endpoints including concentration, memory, quality of life, and social participation. Conclusion We show that online OT is feasible, and that interactive online OT is a promising treatment strategy for affected patients. We present exploratory data on its efficacy and describe variables that can be employed for further investigations in confirmatory trials.